Dinamika Ekonomi Kreatif Berbasis Budaya Reog di Ponorogo Menurut Perspektif Ekonomi Islam - Fitriani, Hanik (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Reog art is one of the local cultural heritages, has great potential in driving the creative economy, especially through the tourism, crafts and arts sectors. From an Islamic economic perspective, this research seeks to understand principles such as justice and balance applied in the development of a creative economy based on local culture. The aim of this research is to analyze the contribution of the reog culture-based creative economy to the local economy in Ponorogo from an Islamic economic perspective. The research method used is a qualitative approach with in-depth interviews, observation and documentation of creative economy actors, arts practitioners and stakeholders in Ponorogo.The research results show that developing a creative economy based on Reog culture is an effective strategy in making a positive contribution to the local economy, in line with Islamic economic principles which emphasize social justice and equal distribution of welfare while maintaining cultural and spiritual values.